Propaganda Dakwah Beraroma Khilafah - Achmad Nur Nur (LPPM Institut Pesantren KH. Abdul Chalim, 2019)
This paper discusses the ideology of Indonesian hizbuttahrir as a transnational Islamic group founded by Taqiyuddin An Nabhani in Jordan who sought to form a Khilafah Islamiyah government in Indonesia. After conducting an in-depth study, there were several findings that led to a spirit of ideology developing rapidly and even coloring the republic. First, there are three stages of propaganda propaganda method consisting of Tatsqif (introduction), Tafa'ul (formation of awareness and general opinion about khilafah), istilamul hukmi (revolutionary movement by building the daulah Islam with the khilafah system). Second, when Islam was made an ideology by HTI indirectly Islam as a message of divinity had entered the ideological realm which contained interests and power. Through this region that Islam is no longer present, but an understanding of Islam, which coloring it. It was at this time that the emotions and fantasies of the religious collective were built even into an undeniable force. When hearing the word HTI, what is reflected in his memory is Islam and that makes no sense. Thus, without any burden and full of public trust, he said that he did not defend HTI but instead defended Islam. One way to get out and survive from propaganda, this paper provides anticipatory offers based on the nationalism of the archipelago king, including social sensitivity, economic independence, as well as culture, justice and peace, togetherness and involvement of intellectuals, government, religious leaders, and communities to exercise control country.